COMPARATIVE ANALYSIS OF THE THEME OF "ALLAH'S INVITATION TO THE THRONE" IN THE WORKS OF "ISHAROTUL-MAROM" AND "SHARHI WASIYA IMAM ABI HANIFA" (Texas Journal of Multidisciplinary Studies, 2022)
In this topic, let's compare Kamaluddin Bayazi's style of covering the issue of "Allah's request to the throne" in his work "Isharatul-Maram" with Akmaluddin Bobarti's treatise "Sharhi Wasiya Imam Abi Hanifa". Why Bayazi did not cite his view, while Bobarti is the opposite, he mainly used intellectual evidence, and Bayazi often cited the views of Ash'ari scholars, and Abu Hanifa's statement on the parable of the "throne" contains a refutation of several erroneous categories. will be reflected.